A pressure-sensitive adhesive made from macca carbon for medical use. Issue 1 (February 2023) - Sakdapipanich, Jitladda; Rodgerd, Phawasoot; Yakkul, Sutaporn; Nijpanich, Supinya
Macca carbon (MC), derived from high-temperature carbonized macadamia nut-in-shell wastes from macadamia nut processing, exhibits a high surface area, high number of electrons, and high efficiency in emitting far-infrared (FIR) radiation at wavelengths between 4 and 20 μm. Numerous inventions have demonstrated promising results in health improvement applications, such as increased blood circulation, less inflammation, and enhanced life expectancy. In this study, MC and a pressure-sensitive adhesive (PSA) were coupled to form a new bandage called an MC cohesive bandage. It was manufactured by combining various quantities of MC powder with PSA and applying it to a spandex fabric tape. The peeling test, water permeability, and skin irritation were examined. The quantity of FIR radiation between 6 and 14 μm and the thermal properties of MC cohesive bandages were investigated. The FIR penetration effectiveness was determined by measuring the temperature rises from the streaky pig skin covered with MC cohesive bandages at various depths.